Advancements in Hybrid Energy Storage Systems for Rural Electrification: A Comprehensive Case Study on Siwa Oasis in Egypt on Increasing Battery Longevity in Standalone PV Systems - Khalid Alqunun; Nehad M. Khattab; Ismail Marouani; Kamel Tlijani; Mohamed Abdelhameed Zaky; Loay Mohamed Ali El-Sayed; Ahmed Ibrahim Omar; Badr M. Alshammari; Tawfik Guesmi; Ahmed Hussain Elmetwaly; Ramy Adel Younis (IEEE Access)
The use of standalone photovoltaic power systems (PVPS) as a viable solution for rural electrification has gained significant momentum. Electricity for essential home requirements is now commonly available thanks to these systems. Typically, PVPS incorporate devices for storing energy, predominantly Lead-acid (LA) batteries, to address the supply-demand disparity inherent in solar energy. However, the limited lifespan of LA batteries results in increased costs for PVPS. To address this issue, researchers have introduced a solution called the supercapacitor-battery hybrid energy storage scheme (HESS). The objective of this approach is to foster the longevity of batteries by minimizing the stress incurred by fluctuations in charging and discharging. Currently, there are a variety of HESS and associated energy management tactics to choose from, each tailored to specific uses. These systems differ in topology, intricacy, and control algorithms. This research article offers a thorough assessment of the latest advancements in the field of HESS and examines various topologies that could potentially increase the longevity of Lead-acid batteries in PVPS. The study includes theoretical analyses and numerical simulations using MATLAB Simulink to evaluate different HESS topologies in rural residential energy systems. The investigation and comparison of the efficacy of these topologies in lowering the impact on the battery is conducted. Additionally, the proposed strategy’s effectiveness is confirmed by assessing the maximum estimated battery lifespan in all potential operation scenarios. Extensive simulation studies were conducted using MATLAB/Simulink to analyze the microgrid’s operation in various scenarios throughout the year. Ultimately, a HESS has been experimentally proven and its effectiveness in a PVPS standalone setting has been simulated in order to confirm the accuracy of the initial analysis.